ANALISIS PENGARUH GWM, EQUITY RATIO, EARNING VOLATILITY, CREDIT RISK, DAN SIZE TERHADAP LIQUIDITY CREATION PADA BANK UMUM DI INDONESIA DENGAN SIZE SEBAGAI VARIABEL KONTROL (Studi Kasus Pada Bank Umum di Indonesia Periode 2010-2014) - Pratama, Raditya Utari Putra; Wahyudi, Sugeng (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this study was to analyze the influence of Reserve Requirement Ratio (RRR), Bank Capital Ratio (EQRAT), Earning Volatility (EARNVOL), Credit Risk, and Size toward Liquidity Creation ten largest Conventional Banks in Indonesia. The sampling technique used in this study is purposive sampling technique with the criteria of ten largest conventional Banks who publish annual financial reports periodically during 2010-2014. The data used in this study was obtained from annual financial reports on the website of conventional Banks with a sample of ten largest conventional Banks in Indonesia. Methods of data analysis in this study with Multiple Regression Analysis, which previously performed classical assumption test. Hypothesis testing using F-statistic test, t-statistical test and the determination of coefficients Adjusted Â with a significance level of 5%. The results of the study are the independent variables simultaneously (F test) effect on Liquidity Creation with a significance level of 0.000. While partially (t test) showed that the variable RRR, EARNVOL, and Size has no significant effect on Liquidity Creation. Variable EQRAT has significant negative effect on Liquidity Creation. Variable Credit Risk has significant positive effect on Liquidity Creation. Adjusted Â is 0.477 which means that the ability of the four independent variables and one control variable can explain Liquidity Creation amounted to 47.7%, while the rest is explained by other factors.